Interaction between 17 α-ethynylestradiol hormone with Langmuir monolayers: The role of charged headgroups - Stunges, Gabriele M. [UNESP]; Martin, Cibely S. [UNESP]; Ruiz, Gilia C.M. [UNESP]; Oliveira, Osvaldo N.; Constantino, Carlos J.L. [UNESP]; Alessio, Priscila [UNESP] (Elsevier, 2017)
The persistence of steroid hormones disposed of in the environment may pose risks to the health of humans and wildlife, which brings the need of understanding their mode of action, believed to occur in cell membranes. In this study, we investigate the molecular-level interactions between the synthetic hormone 17 α-ethynylestradiol (EE2) and Langmuir monolayers that represent simplified cell membranes. In surface pressure isotherms, EE2 was found to expand the monolayers at low surface pressures of the positively charged dimethyldioctadecylammonium bromide (DODAB), zwitterionic 1,2-dipalmitoyl-sn-glycerol-3-phosphocholine (DPPC), negatively charged 1,2-dipalmitoyl-sn-glycero-3-phosphoglycerol (DPPG), and partially anionized stearic acid (StAc). The largest effects were observed for the charged DODAB and DPPG. At the pressure (30 mN.m−1) corresponding to the molecular packing of a cell membrane, EE2 caused the compressibility modulus to decrease, again with the largest changes occurring for DODAB and DPPG. The effects from EE2 on the packing of the lipid molecules at this high pressure depended essentially on the size of the headgroups, with EE2 contributing to the area per lipid for StAc and DODAB, whose headgroups are small. EE2 interacted with the headgroups of all lipids and StAc, also affecting the ordering of the tails for DODAB, DPPG and DPPC, according to in situ polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS). Based on the analysis with the two characterization methods, we propose a model for the EE2 positioning and molecular groups involved in the interaction, which should be relevant to unveil the endocrine disrupting action of EE2.
Keywords: 17 α-ethynylestradiol; Biomembrane model; Langmuir monolayer; Phospholipid; Pm-irras